A numerical model for bird strike simulations in composite aerostructures - Donadon, Maurício Vicente (2008)
The present paper describes the implementation of an improved damage mechanics based material model combined with an equation of state to simúlate the progressive failure in composite aerostructures subjected to bird strike loading. A series of bird strike impacts on flat panels fabricated from low cosí woven glass composite materials are used to valídate the material model for practical composite component applications. The panels are modelled with shell elements only. The proposed material model can capture the strain rate enhancement to strength and strain in shear observed in composite materials. A hydrodynamic model for the bird, based on 90% water and 10% air, is derived to represent the behaviour of the bird for all impact scenarios considered. The bird is heterogeneous in nature. However, a uniform material behaviour is assumed with a geometry based on a 2:1 length to diameter ratio with a cylindrical body and spherical end caps using Lagragian mesh. Appropriate contact definitions are used between the bird and the composite panel. The simulations results are compared to experimental results and conclusions drawn.